Atypical Marginal Zone Hyperplasia is a Mimic for Lymphoma in Pediatric Transplant Recipients: Report of Two Patients. (September 2015) - Caltharp, Shelley A.; Qayed, Muna; Park, Sunita I.
Atypical marginal zone hyperplasia (AMZH) of mucosa-associated lymphoid tissue (MALT) closely resembles lymphoma in that it shows expansion of the marginal zones with prominent intraepithelial B lymphocytes, is immunoglobulin light-chain restricted, and may show aberrant CD43 expression. However, unlike lymphoma, it does not show rearrangement of the immunoglobulin heavy chain gene (immunoglobulin H [IgH]) by polymerase chain reaction (PCR), and it behaves in a benign fashion. We identified AMZH in 2 pediatric solid organ transplant recipients who presented with adenotonsillar hypertrophy. To date, the patients have experienced a self-limited course in the absence of treatment or reduction of immunosuppression. Atypical marginal zone hyperplasia is a pitfall for posttransplant lymphoproliferative disorder and MALT lymphoma in the pediatric solid organ transplant population. In transplant patients with a lambda-restricted B-cell clone and marginal zone hyperplasia in native MALT sites, PCR for IgH and IgK gene rearrangement is essential to prevent misdiagnosis.